Long-term changes of rice yield loss estimated with AOT40 and M7 metrics using comprehensive ozone and rice cultivation data over South Korea - Lee, Jimin; Han, Jin-seok; Park, Jinsu; Ahn, Joon-Yeong; Lee, Gangwoong (Asian journal of atmospheric environment (Online), 2023)
This study examines the change in rice yield due to ozone exposure in South Korea using extended air quality monitoring data from 2000 onwards. Notably, the maximum daily 8-h average O 3 (MDA8O3) showed a substantial annual increase of 1 part per billion by volume (ppbv) from 1990 to 2021. AOT40 (accumulated dose of ozone over a threshold of 40 ppb) levels exceeded set thresholds in the early 2010s, and the M7 (mean 7-h ozone mixing ratio) index exhibited a parallel pattern, with a more pronounced increase than the AOT40 during the same period. Spatial variations of AOT40 and M7 metrics have been assessed annually across South Korea since 2000. Both metrics displayed spatial disparities, with higher values in western regions and lower values in the east. In particular, Dangjin and Seosan counties in Chungnam province experienced the greatest rice yield loss due to extensive rice cultivation area and high ozone exposure metrics. The quantified yield loss due to AOT40 increased from 127,000 in 2000 to 230,000 tonnes in 2021 with an increasing rate of 6500 tonnes per year. M7 indicated a rise in yield loss of 3500 tonnes per year, with yield losses growing from 32,000 in 2000 to 92,000 tonnes in 2021. Despite M7’s lower loss, it demonstrated a higher percentage increase of 188% over two decades, which was double AOT40’s 81%. While the decline in rice production was mainly linked to shrinking cultivation areas, its productivity was improved. Taking both factors into account, there was an unexplained 3% decrease in production over the same period. This discrepancy was close to the 2.5% rice yield loss attributed to the AOT40 metrics, suggesting that the majority of the additional 3% decline in production, surpassing improvements in productivity, could be attributed to the impacts of ozone exposure. We estimated the annual economic loss due to rice yield loss up to around 0.6 billion US dollars, corresponding to an annual rice production loss of 230,000 tonnes using AOT40. It is important to note that this value is expected to steadily worsen as ozone levels increase. This underscores the urgency of taking swift measures to reduce ozone levels, aiming not only to mitigate future economic losses but also to prevent potential health implications.